Technological significance of anatomical features and chemical composition of grain (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
anatomic characteristics of grain, the importance of chemical composition, the amount of the main mineral substances in the grain, relative distribution of substances by anatomical parts of wheat grain